Peroxiredoxin 6 homodimerization and heterodimerization with glutathione S-transferase pi are required for its peroxidase but not phospholipase A(2) activity - Zhou, Suiping (Free Radic Biol Med, 2016)
Peroxiredoxin 6 (Prdx6) is a unique 1-Cys member of the peroxiredoxin family with both GSH peroxidase and phospholipase A(2) (PLA(2)) activities. It is highly expressed in the lung where it plays an important role in antioxidant defense and lung surfactant metabolism. Glutathionylation of Prdx6 mediated by its hetrodimerization with GSH S-transferase π (πGST) is required for its peroxidatic catalytic cycle. Recombinant human Prdx6 crystallizes as a homodimer and sedimentation equilibrium analysis confirmed that this protein exists as a high affinity dimer in solution. Based on measurement of molecular mass, dimeric Prdx6 that was oxidized to the sulfenic acid formed a sulfenylamide during storage. After examination of the dimer interface in the crystal structure, we postulated that the hydrophobic amino acids L145 and L148 play an important role in homodimerization of Prdx6 as well as in its heterodimerization with πGST. Oxidation of Prdx6 also was required for its heterodimerization. Sedimentation equilibrium analysis and the Duolink proximity ligation assay following mutation of the L145 and L148 residues of Prdx6 to Glu indicated greatly decreased dimerization propensity reflecting the loss of hydrophobic interactions between the protein monomers. Peroxidase activity was markedly reduced by mutation at either of the Leu sites and was essentially abolished by the double mutation, while PLA(2) activity was unaffected. Decreased peroxidase activity following mutation of the interfacial leucines presumably is mediated via impaired heterodimerization of Prdx6 with πGST that is required for reduction and re-activation of the oxidized enzyme.